Penerapan Analytical Hierarchy Process (AHP) untuk mempermudah Penentuan Kendaraan Pribadi - . Hendra; . Marzuki (Explore: Jurnal Sistem Informasi dan Telematika (Telekomunikasi, Multimedia dan Informatika), 2012)
In todays modern era, the various types of vehicles being produced to facilitate a person it? carrying out activities throughout the day. One of the vehicles chosen by a handful of people is a car that not only can accommodate several people but also has a dual function that can accommodate luggage in the car. Surely it is not uncommon when someone is having difficulty in choosing the type of car he wanted. In this Final Project, the authors want to design a simple web application using the analytical hierarchy process to select the type of car based on certain criteria. Through the selection criteria that exist in the web application can be determined what kind of car that suits ones choice. This can be determined from charging an application that has been filled by a person in determining the type of criteria to match. Based on the design of web applications is expected to be used for the selection of cars in accordance with appropriate criteria.